2021
DOI: 10.1111/mms.12874
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of common bottlenose dolphin (Tursiops truncatus) over the French Mediterranean continental shelf

Abstract: The common bottlenose dolphin (Tursiops truncatus) subpopulation in the Mediterranean is listed as vulnerable by the International Union for Conservation of Nature. This species is strictly protected in France and the designation of Special Areas of Conservation (SAC) is required under the EU Habitats Directive (92/43/EEC). However, little information is available about the structure and dynamics of bottlenose dolphins in French Mediterranean waters. We collected photo-identification data over the whole French… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The findings about depth preferences agree with studies on bottlenose dolphins [76][77][78][79][80] and shearwaters [24]. However, they differ from other studies in which our focal species prefer offshore waters [81][82][83]. A greater difference in habitat preference was displayed by the species in relation to the seabed index, with seabirds showing the highest presence at 145 m and bottlenose dolphins at 165 m, in agreement with another study in which sightings occurred over steep slopes [84].…”
Section: Discussionsupporting
confidence: 83%
“…The findings about depth preferences agree with studies on bottlenose dolphins [76][77][78][79][80] and shearwaters [24]. However, they differ from other studies in which our focal species prefer offshore waters [81][82][83]. A greater difference in habitat preference was displayed by the species in relation to the seabed index, with seabirds showing the highest presence at 145 m and bottlenose dolphins at 165 m, in agreement with another study in which sightings occurred over steep slopes [84].…”
Section: Discussionsupporting
confidence: 83%
“…In the basin, the species shows a remarkable level of ecological and behavioral plasticity, an erratic distribution, and variable habitat use and residency degrees depending on local conditions, resources availability and social factors (Blasi and Boitani, 2012;Giannoulaki et al, 2017;Vassallo et al, 2020;Pace et al, 2021). Several studies reported different distribution patterns, where individuals may present high site fidelity or, conversely, show movements on a scale of hundreds of kilometers (e.g., Gnone et al, 2011;Pulcini et al, 2014;Pleslićet al, 2019;Pace et al, 2021;Labach et al, 2022). Many environmental factors, physiographic characteristics, and seasonal patterns appear to drive the observed fine-scale coastal distribution and seem to best predict suitable habitats for the species (Blasi and Boitani, 2012;Marini et al, 2015;La Manna et al, 2016;Laran et al, 2017;Giannoulaki et al, 2017;Vassallo et al, 2020;Gnone et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic recordings were collected in an area of approximately 13 km 2 in the French Riviera, characterized by three main habitat types: Posidonia bed, circalittoral coarse sediment and infralittoral sand, with a bottom depth not exceeding 150 m. The bottlenose dolphin population inhabiting these waters has an estimated size of 223 individuals (95% CI = 152-385) 66,67 . The population is connected to adjacent popula- www.nature.com/scientificreports/ tions of the Gulf of Lion and is mainly composed of transient individuals 66,67 . The mean group size is 16 individuals, with a range between 1 and 55 66,67 (Table 5).…”
Section: Port Cros (Pc)mentioning
confidence: 99%